Glutathione: The master antioxidant - Beyond skin lightening agent - Guneet Gandhi; S.K. Malhotra; Tejinder Kaur; Shashank Tyagi; R.L. Bassan (Wolters Kluwer Medknow Publications, 2021)
Glutathione is a thiol-containing tripeptide which is considered as a master antioxidant. Found naturally in fresh leafy vegetables, fruits, and nuts, commercially available preparations of glutathione have been found to be useful in number of medical conditions such as central nervous system disorders, autism, cardiovascular system disorders, peripheral vascular disorders, diabetes and its complications, liver disease, acquired immunodeficiency syndrome/human immunodeficiency virus, and chronic obstructive pulmonary diseases. With regards to the dermatologic disorders, some studies have highlighted the role of glutathione as a skin-lightening agent. The studies on use in other diseases such as psoriasis, pemphigus vulgaris, acne vulgaris, rosacea, etc., are limited and need to be explored more. Glutathione is available as oral preparations (pills, sublingual tablets, solutions, syrups, and sprays), parenteral forms (intravenous [IV] preparations), topical formulations (creams, soaps, and facewashes). The major drawback of oral form of glutathione is its low bioavailability in humans. To overcome this drawback, sublingual tablets and oral liposomal glutathione have been made available. However, the number of studies evaluating its efficacy and safety are less in number. This review article has been written to highlight the role of glutathione in various dermatologic disorders apart from skin-lightening agent.